Lipid environment determines the drug-stimulated ATPase activity of P-glycoprotein - Tran, Nghi N. B.; Bui, A. T. A.; Jaramillo-Martinez, Valeria; Weber, Joachim; Zhang, Qinghai; Urbatsch, Ina L. (Frontiers in Molecular Biosciences, 2023)
P-glycoprotein (Pgp) is a multidrug transporter that uses the energy from ATP binding and hydrolysis to export from cells a wide variety of hydrophobic compounds including anticancer drugs, and mediates the bioavailability and pharmacokinetics of many drugs. Lipids and cholesterol have been shown to modulate the substrate-stimulated ATPase activity of purified Pgp in detergent solution and the substrate transport activity after reconstitution into proteoliposomes. While lipid extracts from E. coli, liver or brain tissues generally support well Pgp’s functionality, their ill-defined composition and high UV absorbance make them less suitable for optical biophysical assays. On the other hand, studies with defined synthetic lipids, usually the bilayer-forming phosphatidylcholine with or without cholesterol, are often plagued by low ATPase activity and low binding affinity of Pgp for drugs. Drawing from the lipid composition of mammalian plasma membranes, we here investigate how different head groups modulate the verapamil-stimulated ATPase activity of purified Pgp in detergent-lipid micelles and compare them with components of E. coli lipids. Our general approach was to assay modulation of verapamil-stimulation of ATPase activity by artificial lipid mixtures starting with the bilayer-forming palmitoyloyl-phosphatidylcholine (POPC) and -phosphatidylethanolamine (POPE). We show that POPC/POPE supplemented with sphingomyelin (SM), cardiolipin, or phosphatidic acid enhanced the verapamil-stimulated activity (Vmax) and decreased the concentration required for half-maximal activity (EC50). Cholesterol (Chol) and more so its soluble hemisuccinate derivative cholesteryl hemisuccinate substantially decreased EC50, perhaps by supporting the functional integrity of the drug binding sites. High concentrations of CHS (>15%) resulted in a significantly increased basal activity which could be due to binding of CHS to the drug binding site as transport substrate or as activator, maybe acting cooperatively with verapamil. Lastly, Pgp reconstituted into liposomes or nanodiscs displayed higher basal activity and sustained high levels of verapamil stimulated activity. The findings establish a stable source of artificial lipid mixtures containing either SM and cholesterol or CHS that restore Pgp functionality with activities and affinities similar to those in the natural plasma membrane environment and will pave the way for future functional and biophysical studies.